2017
DOI: 10.1039/c7sc02205k
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic (salen)ruthenium(iii) anticancer complexes exhibit different modes of cell death directed by axial ligands

Abstract: A cancer-cell selective bis(guanidine)-ruthenium(iii) complex induces apoptosis, whereas its amidine analogue effectively kills cancer cells through paraptosis pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Overall, these data highlighted the crucial role played by the cellular uptake process in determining the anticancer efficacy of Ru(III)-based drugs, showing both POPC and DOTAP-based liposomes as very efficient nanocarriers for the stabilization of Ru complexes in aqueous media and their effective transport in cells. Particularly relevant was their clear detection in the nucleus, differently from other known Ru(III)complexes, able to accumulate in the cytoplasm but not in the nuclear region [153]. Notably, for these systems cationic DOTAP nanoaggregates proved to be more effective as Ru(III)-based drugs carriers, showing faster uptake kinetics [77,79,100,106].…”
Section: Cellular Uptake Studies On Ru(iii)-containing Liposomes By Fmentioning
confidence: 97%
See 3 more Smart Citations
“…Overall, these data highlighted the crucial role played by the cellular uptake process in determining the anticancer efficacy of Ru(III)-based drugs, showing both POPC and DOTAP-based liposomes as very efficient nanocarriers for the stabilization of Ru complexes in aqueous media and their effective transport in cells. Particularly relevant was their clear detection in the nucleus, differently from other known Ru(III)complexes, able to accumulate in the cytoplasm but not in the nuclear region [153]. Notably, for these systems cationic DOTAP nanoaggregates proved to be more effective as Ru(III)-based drugs carriers, showing faster uptake kinetics [77,79,100,106].…”
Section: Cellular Uptake Studies On Ru(iii)-containing Liposomes By Fmentioning
confidence: 97%
“…Particularly relevant was their clear detection in the nucleus, differently from other known Ru(III)complexes, able to accumulate in the cytoplasm but not in the nuclear region. [153] Notably, for these systems cationic DOTAP nanoaggregates proved to be more effective as Ru(III)-based drugs carriers, showing faster uptake kinetics. [77,79,100,106] Overall, analysis of the dansyl-dependent fluorescence emission over time indicated that the HoThyDansRu/DOTAP nanoaggregates first localized within the cell membranes, then entered the cytoplasm, spreading to the whole cell, including perinuclear and nuclear compartments (Figure 8b) [100].…”
Section: Cellular Uptake Studies On Ru(iii)-containing Liposomes By Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Bursch et al [23] showed that inhibition of autophagy inhibited TAM-induced cell death in MCF-7 cells. In another study, autophagosome formation in MCF-7 cells exposed to TAM was imaged through dansylcadaverine, a fluorescent probe of autophagosome [28]. Hwang et al [29] found that autophagy was induced independent of ER as light chain-3-II (LC3-II) increased in ER+ MCF-7 and ER-SKBR-3 breast cancer cells which were exposed to TAM [26].…”
Section: Discussionmentioning
confidence: 99%